A Review on Using Crumb Rubber in Reinforcement of Asphalt Pavement. (30th January 2014) - Mashaan, Nuha Salim; Ali, Asim Hassan; Karim, Mohamed Rehan; Abdelaziz, Mahrez
Abstract : An immense problem affecting environmental pollution is the increase of waste tyre vehicles. In an attempt to decrease the magnitude of this issue, crumb rubber modifier (CRM) obtained from waste tyre rubber has gained interest in asphalt reinforcement. The use of crumb rubber in the reinforcement of asphalt is considered as a smart solution for sustainable development by reusing waste materials, and it is believed that crumb rubber modifier (CRM) could be an alternative polymer material in improving hot mix asphalt performance properties. In this paper, a critical review on the use of crumb rubber in reinforcement of asphalt pavement will be presented and discussed. It will also include a review on the effects of CRM on the stiffness, rutting, and fatigue resistance of road pavement construction.